Defect Analysis Using Failure Mode and Effects Analysis and Fault Tree Analysis: Case Study: Secondary Section PT PID Ongkowijoyo - Pramono, Elvina; Noya, Sunday; Ekawati, Yurida (Teknik Industri Universitas Ma Chung, 2024)
Quality control is a vital aspect of product manufacturing, ensuring adherence to predefined standards and meeting consumer expectations. This study focuses on quality control within the cigarette production process, specifically in PT PID Ongkowidjojo, a prominent manufacturer located in Malang, Indonesia. Despite meticulous production processes, defects in cigarette sticks persist, leading to waste of resources, time, and potential degradation in product quality. The research employs Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA) to identify, analyze, and propose solutions for defects occurring in the maker machine division. Initial analysis reveals common defects such as glue inadequacy, tears in wrappers, and tobacco density inconsistencies, prompting the need for systematic improvements. Through FMEA and FTA methodologies, root causes of defects are pinpointed, and corrective actions are proposed. Implementation of these measures results in a reduction of Risk Priority Number (RPN) values for major defects, indicating a positive impact on production quality. However, limitations in utilizing gate symbols within FTA are acknowledged, suggesting avenues for future research to optimize analytical techniques. This study contributes to the ongoing discourse on quality control in manufacturing industries, particularly in addressing common defects in cigarette production. By integrating FMEA and FTA methodologies, it offers insights into effective defect mitigation strategies, highlighting the importance of continuous improvement in maintaining product quality and operational efficiency.